HUKUM “PATAH TITI” SEBAGAI METODE PEMBAGIAN WARISAN PADA MASYARAKAT ADAT GAYO ACEH TENGAH - RIFQI RIFQI (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. H. M Hasballah Thaib2. Yefrizawati3. Idha Aprilyana Sembiring Customary inheritance law is a method of distributing inheritance to grandchildren who has been suspended earlier than his grandfather, so that the grandchildren cannot be considered as heirs to inherit the inheritance of his grandfather at the time of his grandfather today and Article 185 Compilation of Islamic Law annulled or borrowing the method of distributing the inheritance in Gayo, Central Aceh and approved by the substitute inheritance concept This study uses descriptive analytics using empirical juridical research methods, in order to discuss the legal conflicts in the implementation of Patah Titi as a method of dividing customary inheritance in the Gayo community of Central Aceh against the enactment of Compilation of Islamic Law.The results of the study show that the implementation of Patah Titi customary inheritance law is still carried out by the Gayo indigenous people in Central Aceh, because customary law in the community is not contradictory. Patah Titi method in the distribution of inheritance according to the Compilation of Islamic Law clearly determines at the time of its implementation because it excludes the portion of grandchildren, is not included in the court and legal certainty for grandchildren to obtain inheritance by looking for experts to find related to the world mentioned and called Article 185 Law Compilation Islam, then opens the opportunity for grandchildren who appear as heirs to inherit because the portion is not the same as the portion obtained by heirs while still alive and renewing the law that can be done by heirs who multiply Patah Titi through supporting media adat, among others, through the transition of peace, overcoming the level of Mukim (resolution of the law of appeal), overcoming the level of the Aceh Adat Council and through a lawsuit in the Court of the Aceh Syar'iyah Court. It is better if the Gayo Central Aceh indigenous people continue to carry out the Patah Titi inheritance method as a form of legal awareness that continues to live in their customs. The government asked no one to impose inheritance over grandchildren who were issued first from the world because it would eliminate the existence of adat wari law as the universality of inheritance law and allow the public to settle legal inheritance settlement through deliberations and consensus in helping the inheritance in Gayo, Aceh Tengah.Keyword: Gayo, Inheritance Distribution, Patah Titi, Aceh Tengah.